Longitudinal Impact of Faculty Participation in a Course Design Institute (CDI): Faculty Motivation and Perception of Expectancy, Value, and Cost - Cara Meixner; Elizabeth Ben Ward; Megan Good; Melissa Altman (To Improve the Academy)
Course design institutes (CDIs), which systematically guide faculty through the (re)design of courses, often transpire in an intensive residency or learning community format. Little is known, to date, of the long-term impact of such initiatives, particularly in the context of faculty motivation. This longitudinal study explores changes in faculty attitudes toward teaching, offering insight into the multifaceted gains and limiting factors influencing motivation as conceptualized by the expectancy-value-cost model (Barron & Hulleman, 2015). Findings reveal that CDI engagement bolsters the value placed on teaching, but arrives at a noteworthy cost to faculty. Implications for CTLs and instructional faculty are explored.